The Role of Bank Vouching on Financial Statement Integrity: A Case Study of MBKM Internship Independent - Rahma Dwi Fitriana; Sri Trisnaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the role of bank account vouching procedures in maintaining the integrity of financial statements through a case study of MBKM Internship Mandiri program activities. The method used is descriptive qualitative with a case study approach. Data were obtained from observation of recording and verification of financial transactions, documentation of supporting documents, and interviews with finance, accounting, and taxation staff. Data analysis techniques were carried out through data reduction, data presentation, and conclusion drawing. The results show that vouching is carried out systematically starting from the collection of General Ledger data, matching documents such as vouchers, transfer receipts, bank statements, and budgets, to the preparation of daily bank statements. The discussion shows that the vouching procedure functions not only as a technical control, but also as a strategic measure that strengthens transparency, accuracy of records, and compliance with accounting and taxation principles. Vouching supports documentation completeness and audit readiness, and is an important part of an effective internal control system. It has been shown to improve the accuracy of records and transparency of financial statements, while supporting the company's internal control function. This research confirms the importance of vouching as an effective preventive procedure in the financial control system